Enhanced flotation of hemimorphite: Adjusting mineral surface potential with sodium thiocyanate as activator. (1st September 2021) - Zhou, Hepeng; Yang, Zhizhao; Zhang, Yongbing; Han, Haisheng; He, Kunzhong; Luo, Xianping
Highlights: 1. Sodium thiocyanate used as activator in flotation process for the first time. 2. Sodium thiocyanate has a better activation effect on heteromorphite than that of sodium sulfide. 3. The ambidentate ligand SCN- can chemisorbed on the heteromorphite surface via S or N elements. 4. After Sodium thiocyanate treatment, zeta potential of the heteromorphite was greatly decreased. 5. Sodium thiocyanate can enhance the physical adsorption strength of collector ODA on the mineral surface. Abstract: In this paper, sodium thiocyanate (NaSCN) has been used for the first time as an activator of heteromorphite. In the flotation of heteromorphite, 93% recovery was obtained at the concentration of collector ODA 0.4 × 10–4 mol/L in the presence of NaSCN, while the concentration of collector should be 2.5 × 10–4 mol/L and 0.6 × 10–4 mol/L for the non-activator or Na2S treatment, respectively. The Micro-flotation results showed that heteromorphite can be effectively activated by NaSCN. Nay, the activation effect was better than sodium sulfide, and was slightly affected by activation time. FTIR analysis, Zeta-potential measurements and XPS analysis were conducted to determine the activation mechanism of sodium thiocyanate on heteromorphite. The result of FTIR analysis showed that after NaSCN treatment, the collector ODA can be chemisorbed on the heteromorphite surface via forming zinc-ammonium complex, and physically adsorbed simultaneously by electrostatic attraction. Note that the physisorption effect is more significant. Zeta-potential measurements and XPS analysis showed that the ambidentate ligand SCN − can chemisorbed on the heteromorphite surface via forming zinc-thiocyanate complex anions by S or N elements. What's more, the value of zeta potential of minerals was more negative, which enhanced the physisorption of collector on the mineral surface. Ultimately, the surface hydrophobicity of the heteromorphite was enhanced, and better flotation recovery effect was obtained. The results of this paper can provide a new idea for the activation of minerals.